PRELIMINARY STUDY ON THE PHYSICAL TRAINING OF JUNIOR FOOTBALL PLAYERS 16-18 YEARS OLD IN PRIVATE CLUBS IN THE BUCOVINA AREA - Grosu Bogdan-Marius (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
The analysis of the level of motor (physical) training of the teams included in the finding experiment demonstrates that in most cases, regardless of the training institution, the indices of motor skills development are below the requirements of F.R.F